2015
DOI: 10.1007/s00424-015-1697-1
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of Toll-like receptor 3 increases mouse aortic vascular smooth muscle cell contractility through ERK1/2 pathway

Abstract: Activation of Toll-like receptor 3 (TLR3), a pattern recognition receptor of the innate immune system, is associated with vascular complications. However, whether activation of TLR3 alters vascular contractility is unknown. We, therefore, hypothesized that TLR3 activation augments vascular contractility and activates vascular smooth muscle cell (VSMC) contractile apparatus proteins. Male mice were treated with polyinosinic-polycytidylic acid (Poly I:C group, 14 days), a TLR3 agonist; control mice received sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 55 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Although first identified to be an anti-viral receptor responding to viral dsRNA [8][20] recent studies suggest that TLR3 activation in NK cells elicit cytotoxic effects on cancer [8][17][38] . Other studies also demonstrated that TLR3 activates cellular contractility in non-immune systems [18][21][22] . Since YAP/TAZ are mechano-sensitive and TLR3 has potential anti-tumour capabilities, we reasoned that activation of TLR3 might regulate the subcellular localization of TAZ.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although first identified to be an anti-viral receptor responding to viral dsRNA [8][20] recent studies suggest that TLR3 activation in NK cells elicit cytotoxic effects on cancer [8][17][38] . Other studies also demonstrated that TLR3 activates cellular contractility in non-immune systems [18][21][22] . Since YAP/TAZ are mechano-sensitive and TLR3 has potential anti-tumour capabilities, we reasoned that activation of TLR3 might regulate the subcellular localization of TAZ.…”
Section: Resultsmentioning
confidence: 99%
“…The study of TLR3 signalling in immune cells has thus far mainly focused on its downstream pro-inflammatory effects [7][8][44] . However, the mechanisms associated with TLR3 signalling, for example on cellular contractility, has hitherto remained ambiguous, although reported [18][21][22] . We have previously demonstrated that the presence of cancer cells enhanced intracellular contractility of NK cells which promoted nuclear compartmentalization of Eomes [1] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations